The Existence of Mekarbuana Tourism through The Development of Tourism Products in Increasing Visitors or Tourists: Case Study on Mekarbuana Tourism, Karawang - Sumarni, Neni; Faddila, Syifa Pramudita (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The existence of tourism is a supporter of the economy of a region. Tourism in the village of Mekarbuana is expected to encourage the socio-economic community. The method used in this research was descriptive qualitative, using observation, interviews, and documentation studies and analyzed using three triangulation techniques: method triangulation, data source triangulation and theory triangulation. The research results are the development of tourism products, as well as tourism-supporting products that are conceptualized on the 5A tourism principle. The story of tourism products creates a coffee village. Development of tourism-supporting products in the form of amenity items or souvenirs, namely coffee pudding and coffee cakes.